Analisis Konseptual Aplikasi Linguistik Arab dalam Pembelajaran Bahasa Arab di Era Kontemporer: Kajian Deskriptif-Analitis tentang Teori dan Penerapan Linguistik Arab dalam Pembelajaran Bahasa Modern - Sugino; Waslam; Rohana; Iis Susiawati (STKIP Subang, 2025)
This study employs a descriptive-analytic library research method that explores the theoretical and practical applications of Arabic linguistics in modern language education. The article discusses how the theoretical foundations of Arabic linguistics can be adapted into practical strategies that enhance teaching quality and learning outcomes. The study examines key linguistic components such as phonology, morphology, syntax, semantics, and pragmatics as essential elements in Arabic language learning. These linguistic domains provide a systematic framework for understanding the structure, meaning, and function of language, which are vital for developing communicative competence. Data were obtained from relevant scholarly works on Arabic linguistics, pedagogy, and educational technology to ensure comprehensive theoretical coverage. Findings indicate that integrating linguistic principles into Arabic language instruction enhances learners’ awareness of language structure and meaning, supports the development of communicative competence, and offers a scientific foundation for curriculum design. Moreover, combining linguistic studies with modern pedagogical and technological approaches such as Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), and ICT-based learning makes Arabic language teaching more effective, interactive, and relevant to the digital era. The study concludes that Arabic linguistics serves not only as a theoretical discipline but also as a practical framework for constructing systematic, adaptive, and innovative Arabic language learning in the 21st century. The study contributes to strengthening the theoretical foundation of Arabic language pedagogy and offers a framework for integrating linguistic theory with digital learning innovation.